Customer Segmentation Using the Integration of the Recency Frequency Monetary Model and the K-Means Cluster Algorithm - Alamsyah, Alamsyah; Prasetyo, P. Eko; Sunyoto, Sunyoto; Bintari, Siti Harnina; Saputro, Danang Dwi; Rohman, Shohihatur; Pratama, Rizka Nur (Universitas Negeri Semarang, 2022)
Purpose: This research aims to do customer segmentation in retail companies by implementing the Recency Frequency Monetary (RFM) K-Means cluster model and algorithm optimized by the Elbow method.Methods: This study uses several methods. The RFM model method was chosen to segment customers because it is one of the optimal methods for segmenting customers. The K-Means cluster algorithm method was chosen because it is easy to interpret, implement, fast in convergence, and adapt, but lacks sensitivity to the initial partitioning of the number of clusters. To help classify each category of customers and know the level of loyalty, they use a combination of the RFM model and the K-Means method. The Elbow method is used to improve the performance of the K-Means algorithm by correcting the weakness of the K-Means algorithm, which helps to choose the optimal k value to be used when clustering.Result: This research produces customer segmentation 3 clusters with a Sum of Square Error (SSE) value of 25,829.39 and a Callinski-Harabaz Index (CHI) value of 36,625.89. The SSE and CHI values are the largest ones, so they are the optimal cluster values.Novelty: The application of the integrated RFM model and the K-Means cluster algorithm optimized by the Elbow method can be used as a method for customer segmentation.